Adsorption of Copper Ion from Acidic Wastewater by Local Natural Zeolite - Candra Yulius Tahya; Melanie Cornelia; Tagor M Siregar; Muhammad Ikhsan Taipabu (Walisongo Journal of Chemistry, 2022)
Natural zeolites are available in Indonesia in very large quantities and are available in the market at very affordable prices. The use of zeolite has developed in various fields of industry, water treatment and wastewater treatment. The study on the ability of local natural zeolite to adsorb copper from acidic wastewater from a laboratory in Tangerang has been conducted.  XRD data show that the local natural zeolite consists of mordenite as main mineral and quartz as an accessory mineral. Acid activation of zeolite with HCl 3 M could remove quartz impurities from natural zeolite based on XRD data. Mordenite is one of the most abundant zeolite minerals and commercially used for many purposes including adsorbents, catalyst, fertilizer, and gas separation. The crystallinity of mordenite decreases throughout the process of acid activation and calcination. The calcined zeolite has better copper adsorption ability compared to local natural zeolite without any treatment. The optimum copper adsorption percentage is 14.554% at solution pH of 0.3 by using 10 grams of calcined zeolite in 200 mL of wastewater solution.